2018
DOI: 10.1111/bjh.15091
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated antithombin as anticoagulant reversal in a rat model of cardiopulmonary bypass: a potent and potentially safer alternative to protamine

Abstract: Heparin anticoagulation followed by protamine reversal is commonly used in cardiopulmonary bypass (CPB). As an alternative to protamine, a recombinant inactive antithrombin (riAT) was designed as an antidote to heparin and was previously shown to be as potent as protamine in-vitro. In the present study, riAT was assessed for its ability to neutralize heparin after CPB in a rat model. After 60 min of CPB under heparin, rats received 5 mg/kg protamine, 37.5 mg/kg riAT or phosphate buffered saline (PBS) as placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…24 Since chi-AT displayed residual anticoagulant properties counteracting its performance as an antidote, only ri-AT was selected for a cardiopulmonary bypass study on a murine model. 25 In this latter study, the efficiency and half-time of UFH neutralization proved to be higher than with protamine, without the side effects on hemodynamic parameters and plasma histamine levels generally observed with the FDA-approved antidote. Obviously, further preclinical studies are required to assess the immunogenicity, pharmacokinetics, and safety of the inactivated protein.…”
Section: ■ Context and Challengesmentioning
confidence: 72%
See 1 more Smart Citation
“…24 Since chi-AT displayed residual anticoagulant properties counteracting its performance as an antidote, only ri-AT was selected for a cardiopulmonary bypass study on a murine model. 25 In this latter study, the efficiency and half-time of UFH neutralization proved to be higher than with protamine, without the side effects on hemodynamic parameters and plasma histamine levels generally observed with the FDA-approved antidote. Obviously, further preclinical studies are required to assess the immunogenicity, pharmacokinetics, and safety of the inactivated protein.…”
Section: ■ Context and Challengesmentioning
confidence: 72%
“…Two modified ATs, recombinant-inactivated (ri-AT) and chemically inactivated (chi-AT), were proved to reverse the anticoagulant activity of UFH, LMWH, and fondaparinux in plasma in a global coagulation assay (i.e., thrombin generation assay) . Since chi-AT displayed residual anticoagulant properties counteracting its performance as an antidote, only ri-AT was selected for a cardiopulmonary bypass study on a murine model . In this latter study, the efficiency and half-time of UFH neutralization proved to be higher than with protamine, without the side effects on hemodynamic parameters and plasma histamine levels generally observed with the FDA-approved antidote.…”
Section: Heparin Neutralizationmentioning
confidence: 99%
“…The results obtained in a rat model of CPB showed that (in contrast to protamine) riAT was not associated with adverse events (such as hemodynamic instability and histamine release) but was as potent as protamine in reversing heparin's anticoagulant activity. These properties suggested that riAT could safely replace protamine in a post-CPB anticoagulant/reversal protocol (28). Although riAT is promising, its immunogenicity and safety must be evaluated before it can be considered for therapeutic use in humans.…”
Section: Part I: Modified Antithrombin As a Reversal Agent For Heparimentioning
confidence: 99%
“…10,[15][16][17] Representative examples include small molecules, [18][19][20][21][22] polymers, [23][24][25][26] and proteins. 27,28 In spite of these important advances, currently, there are still no protamine surrogates clinically approved for the neutralization of heparin-based anticoagulants. To date, the most reliable strategy for the development of their antidotes has been the utilization of multivalent binding between the cationic groups of antidotes and the anionic groups of anticoagulants.…”
Section: Introductionmentioning
confidence: 99%